2012
DOI: 10.1128/mcb.00751-12
|View full text |Cite
|
Sign up to set email alerts
|

Increased BRAF Heterodimerization Is the Common Pathogenic Mechanism for Noonan Syndrome-Associated RAF1 Mutants

Abstract: Noonan syndrome (NS) is a relatively common autosomal dominant disorder characterized by congenital heart defects, short stature, and facial dysmorphia. NS is caused by germ line mutations in several components of the RAS-RAF-MEK-extracellular signal-regulated kinase (ERK) mitogen-activated protein kinase (MAPK) pathway, including both kinase-activating and kinaseimpaired alleles of RAF1 (ϳ3 to 5%), which encodes a serine-threonine kinase for MEK1/2. To investigate how kinase-impaired RAF1 mutants cause NS, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 59 publications
3
32
0
Order By: Relevance
“…Dimer formation in wild-type BRaf and transactivation of CRaf by wild-type BRaf are dependent on the interaction with activated Ras via the RBD domain [13]–[15]. CRaf/BRaf heterodimerization levels have been reported to be significantly reduced in BRaf knockdown cells [56]. Therefore, a BRaf protein lacking exon 3 would be expected to be unable to dimerize.…”
Section: Discussionmentioning
confidence: 99%
“…Dimer formation in wild-type BRaf and transactivation of CRaf by wild-type BRaf are dependent on the interaction with activated Ras via the RBD domain [13]–[15]. CRaf/BRaf heterodimerization levels have been reported to be significantly reduced in BRaf knockdown cells [56]. Therefore, a BRaf protein lacking exon 3 would be expected to be unable to dimerize.…”
Section: Discussionmentioning
confidence: 99%
“…Greater RAF1 kinase activity was determined for amino acid substitutions located in CR2, CR3, and at the end of CR3, while mutations affecting residues 486 and 491 impaired kinase activity (Kobayashi et al, ; Pandit et al, ; Razzaque et al, ). Nevertheless, expression of the NS‐associated RAF1 mutants Ser257Leu, Pro261Ser, Pro261Ala, Val263Ala, and Leu613Val as well as Asp486Asn, Thr491Ile, and Thr491Arg resulted in robust ERK activation indicating increased and prolonged signaling through the RAS‐MEK‐ERK cascade (Pandit et al, ; Razzaque et al, ; Wu et al, ). In a recent study, both kinase‐defective and kinase‐activating RAF1 mutants were found to promote heterodimerization with BRAF providing evidence for a common pathogenic mechanism in this NS subtype (Wu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In work by Wu et al, increased heterodimerization with B-Raf was found to be the common pathogenic mechanism for Rasopathy/Noonan Syndrome (NS) C-Raf mutants. 21 More specifically, Wu and coworkers found that NS C-Raf mutants with impaired (D486N) or intermediate (L613V) kinase activities displayed increased heterodimerization with B-Raf. With the use of the R > H mutation as well as Raf depletion experiments, they went on to show that the upregulation in MEK/ERK signaling induced by these NS C-Raf mutants was dependent upon the interaction with B-Raf.…”
Section: Revisiting Raf Dimerization In Human Disease Statesmentioning
confidence: 99%